Determining Routes of Drinking Water Depot Distribution Refill Using the Saving Matrix Method Study Depot RO Supardi - akhmad yasir mubarok; Marenda Kurniawati; Mohammad Edwar Sopan; Tri Ngudi Wiyatno (DEAL: International Journal of Economics and Business, 2024)
In the Refill Drinking Water Depot business, of course, it is very important to distribute refilled water to every consumer, design optimal distribution to save time, transportation costs, as well as effective and efficient distribution channels, AMIU RO Supardi is one of the SMEs engaged in the Water Sector. Drinking Refills, the problem faced by this Ro depot is the needs of consumers and the absence of distribution channels. The purpose of this study is to analyze the optimum distribution route using the saving matrix method. After doing research using the Saving Matrix method, the number of distribution routes can be reduced from 16 routes to 11 routes. The original mileage of 113.76 km can be reduced to 40.21 kilometers, which means the distance can be shortened/saving 65% or about 73.55 kilometers. Decreasing routes results in lower shipping costs. Initial cost Rp. 163,800, down to Rp. 125,025. Thus, there is a saving in the delivery of refilled drinking water of Rp. 38,755 or about 24%.